The use of saliva as a biological fluid in relative bioavailability studies: Comparison and correlation with plasma results - Ruiz, María Esperanza (2010)
The aim of the present study was to present new evidence supporting the use of saliva as a biological fluid in relative bioavailability studies. Carbamazepine was chosen as a model drug because of its suitability for salivary therapeutic drug monitoring and its well-documented plasma bioavailability. A relative bioavailability study of four different immediate release carbamazepine products was performed. Stimulated saliva samples were collected by chewing on parafilm wax and by the spitting method. In vitro dissolution testing of formulations, using 900 ml of 1% sodium lauryl sulphate in water, was also carried out. The in vitro–in vivo correlations obtained in this salivary study were consistent with previous correlations assessed using plasma. These results support the suitability of saliva as the biological fluid in relative bioavailability studies.